Traces of historical tropical cyclones and tsunamis in the Ashburton Delta (north‐west Australia). Issue 6 (16th April 2015) - May, Simon Matthias; Brill, Dominik; Engel, Max; Scheffers, Anja; Pint, Anna; Opitz, Stephan; Wennrich, Volker; Squire, Peter; Kelletat, Dieter; Brückner, Helmut; Walsh, J.P.
Abstract Although the north‐western coast of Western Australia is highly vulnerable to tropical cyclones and tsunamis, little is known about the geological imprint of historic and prehistoric extreme wave events in this particular area. Despite a number of site‐specific difficulties such as post‐depositional changes and the preservation potential of event deposits, both tropical cyclones and tsunamis may be inferred from the geomorphology and the stratigraphy of beach ridge sequences, washover fans and coastal lagoons or marshes. A further challenge is the differentiation between tsunami and storm deposits in the geological record, particularly where modern deposits and/or historical reports on the event are not available. This study presents a high‐resolution sedimentary record of washover events from the Ashburton River delta (Western Australia) spanning approximately the last 150 years. A detailed characterization of event deposits is provided, and a robust chronostratigraphy for the investigated washover sequence is established based on multi‐proxy sediment analyses and optically stimulated luminescence dating. Combining sedimentological, geochemical and high‐resolution optically stimulated luminescence data, event layers are assigned to known historical events and tropical cyclone deposits are separated from tsunami deposits. For the first time, the 1883 Krakatoa and 1977 Sumba tsunamis are inferred from sedimentary records of the north‐western part of Western Australia. It is demonstrated that optically stimulated luminescence applied in coastal sedimentary archives with favourable luminescence characteristics can provide accurate chronostratigraphies even on a decadal timescale. The results contribute to the data pool of tropical cyclone and tsunami deposits in Holocene stratigraphies; however, they also demonstrate how short‐lived sediment archives may be in dynamic sedimentary environments.